Effects of wall configuration on building energy performance subject to different climatic zones of China - Zhang, L.Y.; Jin, L.W.; Wang, Z.N.; Zhang, J.Y.; Liu, X.; Zhang, L.H. (Applied energy, 2017)
(a) Total heating and cooling loads of external wall vs insulation thickness, and (b) determination of optimum insulation thickness. [Display omitted] •The annual heating and cooling loads according to the five climatic zones in China are discussed.•The effects of insulation thickness on building energy saving are studied accordingly.•The optimum insulation thicknesses of external wall are obtained for different climatic zones.•The effects of insulation position on time lag and decrement factor are simulated. Building energy plays a significant role in total energy consumption in China. It is widely recognized that the insulation performance of the external envelops is a critical factor for energy consumption of building air conditioning system. In this study, the effects of building external wall’s insulation thickness and position on the heating and cooling loads of a commercial building studied for five cities from different climatic zones of China, namely, Harbin, Xi’an, Shanghai, Kunming and Guangzhou, are investigated numerically. The wall’s optimum insulation thicknesses of the building simulated in these cities are determined by the life cycle cost analysis (LCCA) method. Meanwhile, the different positions of insulation layer embedded in the wall are investigated in terms of the time lag and decrement factor. The results show that the increase of insulation thickness has a significant effect on the building heating load, inversely it exhibits a relatively small effect on the building cooling load. The analysis indicates that building energy savings vary from different climatic zones. For a given wall insulation and the same building conditions, the largest building energy savings are achieved in Harbin, and energy savings of other cities follow the order of Xi’an, Shanghai, Kunming and Guangzhou. The variation of building energy savings in Guangzhou is insignificant along with the increase of the insulation thickness. Using expanded polystyrene as insulation layer material, the optimum insulation layers of the building in Harbin, Xi’an, Shanghai, Kunming and Guangzhou are founded to be 80mm, 60mm, 40mm, 40mm, and 20mm, respectively.